If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 7) = 48 Reorder the terms: 3(7 + y) = 48 (7 * 3 + y * 3) = 48 (21 + 3y) = 48 Solving 21 + 3y = 48 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3y = 48 + -21 Combine like terms: 21 + -21 = 0 0 + 3y = 48 + -21 3y = 48 + -21 Combine like terms: 48 + -21 = 27 3y = 27 Divide each side by '3'. y = 9 Simplifying y = 9
| 6z-8=-23+z | | -11+6x=25+4 | | 4x-1+2=6 | | 2=13/9+b | | 2=9+b/13 | | 7(8-2b)= | | 8x+27x-9=7(5x+8) | | 3x+2x+9=14 | | 3b^2-18b=b-6 | | 3x+32x-2=7(5x+2) | | 2x^2+2x-25=0 | | -4=r/9-5 | | 3.45+3X=2.1 | | 4x-1=-4+4x | | 6X-25=5 | | 2-6x+36=0 | | 7(2r-4)-7r=7r-28 | | 6-4m=6-9m | | log(4)64=4x-3 | | -4.9x^2+9.9x-5=0 | | -4.9x^2+20x-5=0 | | 5(x-4)+6=-14 | | c=-a+2 | | 5m-3=-3+5m | | F-3.3f= | | u^2+2u+1= | | 8a+c=-7c+16 | | 2g+7=5g-2 | | 2x^2+8x+8=72 | | x^2+11x-30= | | 8-7r=r-16 | | 2x-7=6x+7 |